A Distributed Method for Multiplication of Large Matrices using MSMQ Middleware - Ziafat, Hasan; Babamir, Sayyed Morteza (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2016)
Multiplication of large matrices is time consuming. Although parallel algorithms have been presented to reduce the multiplication time, distributed computing and algorithm mechanism is also able to help us in reducing the time. In this paper, we aim to present a new distributed method for multiplication large matrices using the MSMSQ middleware. The multiplication of the large matrices is used in various engineering fields. We came to a conclusion that the proposed method reduces the multiplication time of large matrices to an adequate level.